Hydration of Concrete: The First Steps. Issue 34 (24th May 2018) - Thissen, Peter; Natzeck, Carsten; Giraudo, Nicolas; Weidler, Peter; Wöll, Christof
Abstract: Concrete is the most important construction material used by mankind and, at the same time, one of the most complex substances known in materials science. Since this mineral compound is highly porous, a better understanding of its surface chemistry, and in particular the reaction with water, is urgently required to understand and avoid corrosion of infrastructure like buildings and bridges. We have gained insight into proton transfer from concrete upon contact with water by applying the so‐called Surface Science approach to a well‐defined mineral, Wollastonite. Data from IR (infrared) spectroscopy reveal that exposure of this calcium‐silicate (CS) substrate to H2 O leads to dissociation and the formation of OH‐species. This proton transfer is a chemical reaction of key importance, since on the one hand it triggers the conversion of cement into concrete (a calcium‐silicate‐hydrate phase), but on the other hand also governs the corrosion of concrete. Interestingly, we find that no proton transfer takes place when the same surface is exposed to methanol. In order to understand this unexpected difference, the analysis of the spectroscopic data obtained was aided by a detailed, first‐principles computational study employing density functional theory (DFT). The combined experimental and theoretical effort allows derivation of a consistent picture of proton transfer reactions occurring in CS and CSH phases. Implications for strategies to protect this backbone of urban infrastructure from corrosion in harsh, aqueous environments will be discussed. Abstract : Concrete evidence : A combined experimental and theoretical effort allows derivation of a consistent picture of proton transfer reactions occurring in calcium silicate and calcium silicate hydrate phases. This may have implications for strategies to protect this backbone of urban infrastructure from corrosion in harsh, aqueous environments.